Marine Microalgae of Bangladesh: Nutritional Profile and Application - Zahidul Islam; Jakia Hasan; Turabur Rahman; Shafiqur Rahman (Science and Technology: Developments and Applications Vol. 1, 2024)
Microalgae are an important part of the ecosystem that absorbs carbon dioxide and produces oxygen. They also have potential use in the fields of food, feed, biofuels, pharmaceuticals, and nutraceuticals. This chapter has described the growth, nutritional, and application of five selected commercially important microalgae (Chaetoceros sp.; Isochrysis sp.; Skeletonema sp.; Nannochloropsis sp.; and Tetraselmis sp.) of Bangladesh. The species were isolated from the Bay of Bengal, Bangladesh and experimental culture and analysis were performed in Live Feed Laboratory, Bangladesh Fisheries Research Institute, Marine Fisheries and Technology Station, Cox’s Bazar, Bangladesh. The morphological/external characters were observed under a microscope. The mass culture of the selected species was performed using the F/2 Guillards medium. The key external identifying characters are summarized. The growth cycle and nutritional profiling (protein, lipid, carbohydrate, amino acid, fatty acid) were performed and computed for each species. The chapter provides essential morphological identification features and nutritional profiles for each species. This information is important for industrial and local users, as it aids in understanding the characteristics of each species, ultimately facilitating the selection of target species.